Creativity in science education: definition and constraints - Omar, Siti Salbiah (2015)
The development of Higher Order Thinking Skill (HOTS) in teaching and learning Science in schools is one of the desired goals by many countries. HOTS including creativity will produce better lifelong learning and it is listed among the four main skills needed to face the challenges of the 21st century world of work by American Management Association (2010). However teaching and learning Science particularly more emphasis on the facts, vocabulary, definitions, algorithms and rote learning which is not geared towards the development of creativity. In Malaysia, teachers still practicing teaching methods that do not encourage creativity and consequently the level of creativity among science students is low. Therefore, this paper discuss about the creativity in science education and constraints related to scientific creativity. All this issues will be discussed based on the literature from previous finding.